THE CHARACTERISTICS OF LOW-CODE AND NO-CODE TOOLS AND THEIR IMPACTS ON THE CURRENT MARKET - de Souza Máximo Rodrigues, Felipe; Scombatti Pinto, Giuliano (Revista Interface Tecnológica, 2025)
Low-code tools offer an intermediary solution between flexibility and ease of use, speeding up the development process, while No-code tools democratize development, making it accessible to a broader audience without the need for manual coding. The aim of this study is to explore the impact of Low-code and No-code tools on software development, addressing their definitions, analyzing their characteristics, similarities, and differences, as well as exploring how they influence the market and professional formation. The methodology used is bibliographic research. The results made it possible to identify the importance of these innovations in the rapid delivery of technological solutions and in the transformation of the educational landscape for IT professionals. Both approaches have advantages, such as speeding up development and democratizing the process, but they also present challenges, such as complexity limitations. It was concluded that, despite the challenges, the two tools discussed are catalysts for significant change, shaping the present and future of software development, and should be closely monitored by those seeking efficiency and adaptability in the technology industry.
Keywords: Development; Low-code Tools; No-code Tools; Innovation